Letter to the editor. Discussion of the article by A.A. Zarubin, E.S. Filippov, A.S. Vanyarkina, O.G. Ivanova, A.A. Shishkina “Comparison of Uncontrolled and Device-Induced Therapeutic Hypothermia in Newborn Infants with Hypoxic Ischemic Encephalopathy”, published in Acta biomedica scientifica. 2021; 6(1): 88-93. doi: 10.29413/ABS.2021-6.1.13 - V. A. Shcherbak; V. V. Kocherova (Acta Biomedica Scientifica)
The article presents a discussion of the study results of the effectiveness of treatment of newborns infants with hypoxic ischemic encephalopathy using device-induced therapeutic hypothermia which were obtained by a group of researchers (Zarubin A.A. et al.) in comparison with the results of Russian and foreign researchers.